How Do Drivers Hold Their Phone? Age, Prevalence, & Handedness. (December 2020) - Roady, Trey; Wilson, Kyle; Kuo, Jonny; Lenné, Michael G.
Objective: Research shows frequent mobile phone use in vehicles but says little regarding how drivers hold their phone. This knowledge would inform countermeasures and benefit law enforcement in detecting phone use. Methods: 934 participants were surveyed over phone-use prevalence, handedness, traffic-direction, and where they held their device. Results: The majority (66%) reported using their phone while driving. Younger drivers were more likely to use their device. Of device-users, 67% preferred their passenger-side hand, 25% driver-side, and 8% both. Height- wise: 22% held in-lap, 52% even with the wheel, and 22% at wheel-top. Older drivers were more likely to hold the phone in the highest position The three most popular combinations were passenger-middle (35%), passenger-low (19%), and passenger-high (13.9%). There was insufficient evidence of differences based on handedness, prevalence, or traffic-direction. Conclusion: Driver-preferred attention regions often require substantial neck flexion and eye-movement, which facilitates distraction detection. However, behavior may change in response to future interventions.